The Correlation between Food Security with Stunting Toodler from Fisherman Family - Islamiah, Warda Eka; Nadhiroh, Siti Rahayu; Putri, Endah Budi Permana; Farapti, Farapti; Christiwan, Chyntia Apris; Prafena, Priskila Kris (Media Gizi Indonesia, 2022)
The food insecurity problem is closely related to poverty. One of the communities belonging to the lower middle class in Indonesia is Fishermans. Stunting toddler is one of the chronic nutritional problems caused by low access to and affordability of food. Food and nutrition security is a unity, where nutrition is a very important element in improving the life quality of the population. The purpose of this study was to analyze the relationship between family characteristics, toddler characteristics, and food security with the incidence of stunting in toddlers. This research is included in the cross-sectional study design. The research sample was 87 fisherman households in the Ngemplakrejo Village, Pasuruan City, which were randomly selected using simple random sampling. Data were analyzed using chi-square correlation tests. The results showed that the stunting prevalence was still high at 43.7%. In addition, families in the category of severe food insecurity were also found, namely 16.1%. Based on the study results, there was a relationship between household food expenditure (p=0.027), birth body length (p=0.027), exclusive breastfeeding history (p=0.034) and household food security (p=0.000) with stunting in toddlers. The conclusion of this study is stunting in toddlers can occur due to factors such as family characteristics, toddler characteristics, and food security. This study recommends increasing in food security by paying attention to the adequacy of family food needs through coping strategy, household expenditure by prioritizing toddler nutrition and increasing household food security by providing training and skills in diversification of catch products and productive businesses.